QCD processes and hadron production in high energy e+e- annihilation - Burrows, P (1988)
A study is presented of general features of the reaction e+e-→ hadrons. The data are interpreted in terms of current models of the underlying QCD and hadronisation processes. These models are outlined in detail and their predictions are compared with most of the available experimental data collected between 12.0 and 46.8 GeV mean centre of mass energies. The model arbitrary parameters were optimised to give a generally good description of the global properties of the large hadronic event sample accumulated by the TASSO detector at 35 GeV: The Lund O(α2s) model describes properties in the event plane very well, but is deficient in the properties transverse to this plane. The Webber LLA model gives a good description of the transverse observables, but overestimates those quantities in the plane. The Lund LLA + O(α2s) model provides a good representation of the transverse properties but underestimates some quantities in the plane, though the discrepancy is much smaller than for the LLA model. The evolution of the observables as a function of c.m. energy between 12.0 and 41.5 GeV is generally well described, the Lund LLA + O(α2s) model representing the data best. It is concluded that this model is successful in reproducing accurately most features of the data because it includes QCD calculations of both hard and multiple soft gluon emission processes. The model predictions are extended up to W = 200 GeV, where the two parton cascade models give similar predictions of the event properties which differ significantly from those of the 0(α2s) model. Top quark production is simulated at W = 200 GeV for a top mass of 60 GeV/c2 and the distributions of thrust, aplanarity, PTin,PTout and rapidity are found to be most sensitive to its presence. The data at 35 GeV are also analysed in terms of explicit multijet final states and compared with the QCD model calculations. The 0(α2s ) model is unable to account for the observed rates of 4- and 5- jets per event, though it reproduces the 2- and 3- jet rates reasonably well. The LLA model gives a better description of the rates of ≥ 4-jets but gives too few 3-, and too many 2-jet events. The LLA + O(α2s) model is able to reproduce all jet rates well. All the models describe the trend of the evolution of the jet rates between <√s> = 14 and 43.8 GeV. It is shown that the rate of 3-jet events seen in the data decreases as s increases in a manner consistent with the Q2 dependence of αs as predicted by QCD.